Carol Shields's The Republic of Love: Being, Becoming, Belonging - Polić, Vanja (2007)
The paper explores the connection of myth, romance and identity in Carol Shields's novel "The Republic of Love" with special focus on the notion of identity as fluid and ever-changing, closely related to the notion of geographical space which an individual inhabits.